Theopoetic Folds : Philosophizing Multifariousness - Fackenthal, Jeremy; Faber, Roland, 1960- (Book collections on Project MUSE., 2013)
The chapters in this book explore how the term theopoetics contributes to cutting-edge work in theology, philosophy literature, and sociology.